Delay Identification of the HVAC Project on West Madura Offshore Oil Company Using the House of Risk Method - Gunawan Kunto Bhasworo; Ervina Ahyudanari (IPTEK Journal of Proceedings Series, 2020)
This research is focused on the analysis of delays or risks to the implementation of the "Procurement and Installation HVAC Installation" contract at West Madura Offshore Oil Company, which has a working area in the Offshore area. This study uses the HOR (House of Risk) method as an alternative to the ISO31000: 2009 risk management method that has been used internally by West Madura Offshore Oil Company The basis for selecting the HOR (House of Risk) method is the existence of a tool to see the impact (severity) and relations (relations) between the event of a delay and the factoring agent. In identification of the cause of the delay the method used are collecting data primary through Focus Group Discussion between Internal Expert and Secondary data which use project data for Offshore HVAC Project in the period of the year 2016-2018. The HOR (House of Risk) method in conducting this process is presented as follow review historical data and related document, Focus Group Discussion as information gathering techniques, Risk analysis and Risk Register. There are five significant risks from the results of research using the HOR (House of Risk) method, namely Poor-quality shop and coordination drawings, weather constraints, limited quantity and quality of HR (contractors and subcontractors), Absence of duct fabrication workshops at the site and lack of communication between contractor and subcontractor.